Il progetto nei borghi abbandonati - Eccheli, Maria Grazia; CAVALLO, CLAUDIA (Studi e saggi, 2022)
In these harsh lands inhabited by the silence of humble fragments, architectural design ties both history and life together, revealing the essential features of the place. The book proposes a journey within abandonment between Architecture and ruins: it reinterprets the pioneering research of Aldo Rossi; it explores, together with Gianandrea Gazzola, the labyrinths of meaning between Art and ruin; it investigates the projects of Colletta di Castelbianco by Giancarlo De Carlo and the houses in the Canton of Ticino by Buchner Bründler; and finally, it traces an itinerary of contamination between anonymous architecture and architectural languages in the Mediterranean. It is within these horizons that the Design and Research Laboratory of the Florence School of Architecture reveals the deep soul and redesigns a new life for the abandoned villages of Castiglioncello di Firenzuola (FI) and Campo di Brenzone (VR).